2004
DOI: 10.1152/japplphysiol.00954.2003
|View full text |Cite
|
Sign up to set email alerts
|

Human muscle sarcoplasmic reticulum function during submaximal exercise in normoxia and hypoxia

Abstract: In this study, the response of the sarcoplasmic reticulum (SR) to prolonged exercise, performed in normoxia (inspired O(2) fraction = 0.21) and hypoxia (inspired O(2) fraction = 0.14) was studied in homogenates prepared from the vastus lateralis muscle in 10 untrained men (peak O(2) consumption = 3.09 +/- 0.25 l/min). In normoxia, performed at 48 +/- 2.2% peak O(2) consumption, maximal Ca(2+)-dependent ATPase activity was reduced by approximately 25% at 30 min of exercise compared with rest (168 +/- 10 vs. 126… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 45 publications
1
36
0
Order By: Relevance
“…It should be noted that in previous papers from our group (13,44,50), estimates of Ca 2ϩ uptake and Ca 2ϩ release were 100 times too high. This occurred because of errors in the software used to calculate [Ca 2ϩ ]f in conjunction with a dilution error.…”
Section: Participantsmentioning
confidence: 84%
See 2 more Smart Citations
“…It should be noted that in previous papers from our group (13,44,50), estimates of Ca 2ϩ uptake and Ca 2ϩ release were 100 times too high. This occurred because of errors in the software used to calculate [Ca 2ϩ ]f in conjunction with a dilution error.…”
Section: Participantsmentioning
confidence: 84%
“…Numerous studies have found this to be the case (3,5,13,31,50). Moreover, the reduction in Ca 2ϩ uptake appears to be mediated by reductions in Ca 2ϩ -ATPase activity (3,5,13,50), which appears to occur secondary to modifications in the region of the adenine nucleotide of the enzyme (34,35). These measurements, which are performed in vitro under supposedly optimal conditions by using exogenously generated ATP (47), support the hypothesis that the loss of catalytic activity occurs not as a result of deficiencies in ATP availability but, rather, as a result of structural modifications to the enzyme.…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…With the exception of the tissue samples, all other procedures and measurements were performed during the 3-day exercise protocol. We have previously reported that providing exercise patterns and dietary habits are not substantially altered, a wide range of muscle cellular properties remain stable over a similar time frame (15,69).…”
Section: Experimental Conditionsmentioning
confidence: 99%
“…For the Ca 2ϩ -ATPase, the reaction mixture (pH 7.0) contained 200 mM KCl, 20 mM HEPES, 15 mM MgCl2, 1 mM EGTA, 10 mM NaN3, 5 mM ATP, 0.3 mM NADH, 10 mM phosphoenolpyruvate (PEP), 18 U/ml LDH, 18 U/ml pyruvate kinase (PK), and 25 l homogenate. Enzyme activity was measured using a spectrophotometric method (45), as modified by our laboratory (9). All samples were measured in duplicate at 37°C.…”
Section: Subjectsmentioning
confidence: 99%